LITERATUR REVIEW: GAMBARAN PENGETAHUAN, SIKAP TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA SEKOLAH DASAR - Trisna Apriyani (CV. Adiba Aisha Amira, 2024)
Background: At this time, health issues, especially regarding clean and healthy living behavior, really need to be paid attention to, especially for elementary school age children. Because by living a lively and healthy lifestyle, children will be able to carry out their activities well. Objective: The aim of this literature review is to describe clean and healthy living behavior in elementary school age children. Method: This research method uses the literature review method of articles from internet media. Results: research results for clean and healthy living behavior, from 7 articles it has shown clean and healthy living behavior, but for 3 articles it is still said to be not good, because it is still not enough to carry out clean and healthy living behavior Suggestion: learning experience to create conditions which is good for yourself, your family and society. Students and the school community are expected to be able to carry out PHBS behavior, because if they carry out clean and healthy living behavior it will create a healthy school.